2004
DOI: 10.1200/jco.2004.02.154
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer With Mutation in BRAF, KRAS, and Wild-Type With Respect to Both Oncogenes Showing Different Patterns of DNA Methylation

Abstract: In CRC, the methylation status of multiple promoters can be predicted through knowledge of BRAF and, to a lesser extent, KRAS activating mutations, indicating that these mutations are closely associated with different patterns of DNA hypermethylation. These changes may be important events in colorectal tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
196
2
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(215 citation statements)
references
References 16 publications
15
196
2
2
Order By: Relevance
“…KRAS mutation, as well as low/indeterminate levels of MSI and CIMP, has been associated with methylation of MGMT by several authors. 21,22,42,43 In our study, we found that some KRAS-mutated carcinomas were associated with MGMT immunohistochemical loss of expression (borderline significance), MGMT methylation, and MSI-low/indeterminate phenotype. Of note, we found poor correlation between MGMT immunohistochemical loss of expression and MGMT methylation, as reported by others in colorectal carcinoma and glioblastoma.…”
Section: Discussionmentioning
confidence: 53%
“…KRAS mutation, as well as low/indeterminate levels of MSI and CIMP, has been associated with methylation of MGMT by several authors. 21,22,42,43 In our study, we found that some KRAS-mutated carcinomas were associated with MGMT immunohistochemical loss of expression (borderline significance), MGMT methylation, and MSI-low/indeterminate phenotype. Of note, we found poor correlation between MGMT immunohistochemical loss of expression and MGMT methylation, as reported by others in colorectal carcinoma and glioblastoma.…”
Section: Discussionmentioning
confidence: 53%
“…The concomitant existence of BRAF mutations or MLH1 promoter hypermethylation in LS patients has been extensively documented. 10,11,13,16,[18][19][20][21][26][27][28] The clinical usefulness of MLH1 hypermethylation analysis relies, in part, on the low prevalence observed. MLH1 hypermethylation analysis does not only outperform BRAF mutation analysis but it is also more cost-effective, in terms of incremental cost per additional MLH1 mutation carrier detected.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] However, the identification of hypermethylation in a limited number of LS tumors has made its use controversial. 10,[26][27][28] Issues that affect screening include the accuracy, sensitivity, and specificity of the test, the benefit to the patient, the possible negative ramifications of the results, and the cost. 8,[29][30][31] Before routine implementation in the clinical setting, it is critical to assess the analytical and clinical validity and the cost-effectiveness of BRAF mutation and MLH1 promoter hypermethylation.…”
Section: Introductionmentioning
confidence: 99%
“…The BRAF V600E mutation also increases NF-kB signaling (Ikenoue et al, 2003). This mutation is found in serrated polyps but not in adenomas (Kambara et al, 2004) and displays a striking correlation with MSI-H and CIMP (Nagasaka et al, 2004). KRAS mutations are found in a wider spectrum of early lesions, but never together with BRAF V600E, and are possibly caused by a defect in the MGMT repair gene (Esteller et al, 2000).…”
Section: Discussionmentioning
confidence: 99%